Perancangan Dan Implementasi Jaringan Komputer Dengan Studi Kasus Di SMK Muhammadiyah 2 Sragen - Munandar, Ari, Agus Ulinuha, ST., MT., Ph.D, Dedi Gunawan S.T., M.Sc (2015)
The design of computer networks is of very important in the institution applying computer systems management. Computer network design should match the needs of the institution. The institutions ussing computer network are the institution of education, especially schools. The school uses computer network to manage the administration and the teaching and learning process, so that the use of the internet is needed. The speed of internet access can affect school performance, therefore the bandwidth management in the computer network should be done so that the speed of internet access can be optimized. Using router will be the solution to the problem. This research uses simulation method and implementation. Data collection uses literature review, observation and interview. The design of computer networks in SMK Muhammadiyah 2 Sragen will be simulated using cisco packet tracer based on the data available (analysis of requirement). The results of the design will be implemented directly at SMK Muhammadiyah 2 Sragen. The results of this research is design a new network to replace the existing network. The new developed network to solve the problems from the existing network, from internet connection that has not spread into the room who need access to the internet and bandwidth management that has not been implemented in the network. The design is done as simple as possible to ease for developing of school management.